KAJIAN PERESEPAN ANTIBIOTIKA PADA PASIEN DEWASA DI SALAH SATU PUSKESMAS KOTA YOGYAKARTA PERIODE JANUARI - APRIL 2010 - Muhammad Muhlis (Universitas Ahmad Dahlan, 2011)
To achieve optimal therapy of antibiotics isonefactor supporting the accuracy inprescribing antibiotics errors in prescribing can cause lack of rationality in the use ofantibiotics . Antibiotic was commonly used in the clinicor in private practice doctorsbut also in the centers of other health services such as polyclinics and hospitals theaim of this study is to assess antibiotic prescribing patterns and the level ofrationality the use of antibiotics in adult patients at one center of Yogyakarta on thebasis of data prescriptions. This Study used descriptive design with retrospective datacollection The data was collected from January to April 2010 Data source is aprescription of antibiotics in adult patients We analyzed the antibiotics prescription inthe study based on the selection appropriate dos age frequency and duration. Werecruited 320 patients receive ing antibiotics. The of antibiotics used were amoxicillin64.5 % ampicillin 11.3 % kontrimoksazol 15.9% chloramphenicol 0.6 % metronidazole2.8 % and etracycline 49 % Most of the Patients received a single antibiotic 97.9 %),while the remaining patients received a combination of antibiotics 2.1 % Allprescribing meet appropriate dosage, and frequency except cotrimoxazole (98%) andampicillin 49%). All prescriptions (100%) improper duration. In general antibioticsprescription for adult patients at one health center in Yogyakarta City is comply withthe standard use of antibiotics in Public Health Centers. However, the duration ofantibiotic utilization still became the perspective of the health providers in PublicHealth Centers.